Expected Inflation and Interest Rates in a Multi‐asset Model: A Note - MITCHELL, DOUGLAS W. (Journal of Finance, 1985)
ABSTRACT This paper analyzes the effect of expected inflation on nominal interest rates, in a theoretical model with money and two different bond types. The inclusion of three assets instead of the usual two causes the effect of expected inflation on the interest rates to deviate from unity. Depending on the sizes of the wealth and interest rate effects on the various asset demands, the effect of expected inflation could even be negative. Several special cases are also considered, and the implications for the interpretation of empirical results are discussed.